Potential Analysis and Policy Development in Increasing the Competence of Geography Teachers in the West Pasaman (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
ABSTRACT: This study aims to determine the competency status of geography teachers in West Pasaman, determine the potential for increasing the competence of geography teachers in West Pasaman and to find out the policies implemented to increase the competence of geography teachers in West Pasaman. This type of research uses a qualitative descriptive method. The informants in this study consisted of 5 people who were included in the expert qualifications who had a deep understanding of the state of competence of geography teachers in West Pasaman. The analytical techniques used are Multidimensional Scaling (MDS) and Interpretative Structure Modeling (ISM). The results of this study stated that the competency condition of the geography teacher at West Pasaman High School had an assessment score for each competency in the pedagogical competence obtaining a score of 66, in professional competence obtaining a value of 70, in social competence obtaining a value of 80 and in personality competence obtaining a value of 82.8. competencies that must be improved are as follows; on pedagogic competence a) Mastering the characteristics of students b) Mastering learning theory and educational principles of learning. c) Develop curriculum d) Organize educational development activities. e) Utilizing information and communication technology, f) Facilitating the development of students' potential, g) Utilizing the results of assessment and evaluation for the benefit of learning, and h) Performing reflective actions. On personality competence; a) Demonstrate high work ethic and responsibility. On social competence, a) Developing public speaking skills. On professional competence, a) Develop learning materials. b) Develop professionalism in a sustainable manner, c) Utilize information and communication technology to communicate and develop oneself, d) Keep up with the latest curriculum developments, e) Participate in a driving teacher program and f) Actively participate in digital platforms. There are three sub-elements with the highest driver power values, namely: a) Sub-element 4, Training on the preparation of learning administration; b) sub element 7, Supervise; c) sub element 8, Socialization of the driving teacher program. Based on the graph of the relationship between driver power and dependence, it shows that the three sub-elements are in quadrant IV, this means that these three sub-elements have a high driving force in the policy element for increasing the competency of the West Pasaman High School geography teacher.